A phased splitting off from the high-strength concrete by an electro-blasting method; AIP Conference Proceedings; Vol. 1772 : Prospects of Fundamental Sciences Development (PFSD-2016) - Voitenko N. V. Nikita Valerievich (High energy processes and external exposure of materials, 2016)
Title screen